Analisis Feminis atas Agensi Perempuan dan Kekuasaan Patriarki dalam Cerita Rakyat Paser: A Feminist Analysis of Women’s Agency and Patriarchal Power in Paser Folklore - Azahra, Alfyza Nayla; Ulwatunnisa, Marwah (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2026)
This study examines the representation of women, power relations, and female agency in Paser folklore using a feminist literary perspective. This study focuses on two folktales, namely